The Role of Memorial Places in the Culture of the Holocaust Memory: Guidelines for Understanding and Research Methods - Vitkus, Hektoras (Genocidas ir rezistencija, 2006)
This article analyses the ideas defining the role of memorial places that are relevant to research concerning the development of Holocaust memory in Lithuania. In referring to various concepts and ideas, the author states that the culture of Holocaust memorials must be analysed as a coherent, purposeful and a formalised system. He points to the following consistent patterns of Holocaust memorial development: 1) the system of the Holocaust memorial places developed according to the political, ideological, and cultural trends of official historical memory; 2) the culture of Holocaust memorials developed in accordance with the processes of systematic adaptability, systematic purpose, systematic integration, and systematic auto-modulation; 3) the functions of the Holocaust memorials were formed according to the needs of cultural development within official historical memory: 4) the development of the Holocaust memorials helped bring to maturity certain values of historical memory and a unique ethics to provide meaning to the memorials themselves.The author explains the cultural structure of the Holocaust memorials' in terms of structure, values, psychological factors and ideas of function and process. According to the notion of structure, the functionality of the Holocaust memorial place system is determined not by quantitative value of the artefacts, but their qualitative connections. Considering the concept of value within this system, its specific symbols and historical images give meaning to the material artefacts of Holocaust memory. In terms of the psychological factor, the perception of the Holocaust memorials depends on the institutes which form the socio-cultural historical mentality. Finally, taking into account the process- functional conception, the system of the Holocaust memorial places may differ according to changes in the modelling processes of collective historical memory.In the author's opinion, Holocaust memorials are not authentic sources for knowledge about the historical events of the Holocaust. Rather, they are documents witnessing the development of Holocaust memory, conforming to changes in cultural memory. Holocaust memorials do not create historical knowledge; they take this knowledge from the historical ideology prevailing in the society, which influences individuals, groups, and the forms of communication of Holocaust memory. For these reasons, the culture of Holocaust memorials suffers restrictions according to the policy of a specific society's historical memory.
Keywords: Holocaust; memorialisation; memory politics; memory culture